Dosaje etílico en personas detenidas en el Complejo Policial Cap. P.N.P. Alcides Vigo Hurtado de Trujillo, por cometer actos delictivos, julio-septiembre de 2016 - Aguilar Rodríguez, Carlos Neil (2017)
The objective of the report was to determine the ethyl dosage in the Laboratory of Chemistry and Toxicology of the police complex Cap. P.N.P. Alcides Vigo Hurtado between July and September of 2016. Shefftel Modified method was used, using a total of 381 urine samples of detainees, received in the weighing area of said police unit. 34% were positive for ethyl dosage, of which 93% were men and 7% women, the districts with the highest percentage of positive cases were Trujillo 47%, La Esperanza 19% and El Porvenir 14%. The most frequent crimes committed by the subjects were the crime against property (theft) with a percentage of 35%, followed by the crime against life, the body and health with 21% and crime of violence and resistance to authority with 17%, the month with the most cases was August, with 37%. It was concluded that of the 381 urine specimens of persons arrested, 121 had a positive ethyl dosage, equivalent to 34%.